2020
DOI: 10.1096/fj.202001819r
|View full text |Cite
|
Sign up to set email alerts
|

Lin 28A/Occludin axis: An aberrantly activated pathway in intestinal epithelial cells leading to impaired barrier function under total parenteral nutrition

Abstract: Disassembly of tight junctions is a major cause of intestinal barrier dysfunction under total parenteral nutrition (TPN), but the precise mechanisms have not been fully understood. Normally, RNA binding protein Lin 28A is highly restricted to embryonic stem cells and dramatically decreases as differentiation progresses; however, in our preliminary study it was found aberrantly increased in the intestinal epithelial cells of TPN rats, and thus its mechanism of action needs to be addressed. Herein, we report a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Among them, the reduction or redistribution of claudin-3 is associated with increased intestinal permeability, 36 and occludin is a protein component of tight junctions, the removal or reduced expression of it will lead to loss of the intestinal barrier, that is, the lower the occludin, the more permeable the gut is. 37 , 38 Zonulin family peptides (zonulin) are potent regulators of tight junctions in the gut, and zonulin levels are positively correlated with gut permeability. 39 , 40 The results showed that the proportion of positive cells of CLDN3 and occludin in probiotics and/or nanovaccines treated groups was higher than that in the PBS control group ( Figures 5 and 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the reduction or redistribution of claudin-3 is associated with increased intestinal permeability, 36 and occludin is a protein component of tight junctions, the removal or reduced expression of it will lead to loss of the intestinal barrier, that is, the lower the occludin, the more permeable the gut is. 37 , 38 Zonulin family peptides (zonulin) are potent regulators of tight junctions in the gut, and zonulin levels are positively correlated with gut permeability. 39 , 40 The results showed that the proportion of positive cells of CLDN3 and occludin in probiotics and/or nanovaccines treated groups was higher than that in the PBS control group ( Figures 5 and 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the past 50 years, PN has become a standard-of-care, lifesaving clinical support therapy for premature infants as well as patients who cannot tolerate EN, and particularly TPN has been the only approach of nutritional support for those patients with severe intestinal failure. However, despite the significant clinical benefit of PN, evidence is also accumulating that exclusive PN or TPN may lead to increasing associated risks of exacerbating intestinal injury, due in part to reduced gastrointestinal blood flow and the disruption of intestinal homeostasis, including villus atrophy [15,16], decline in mucosal immunity [17,18] and disassembly of tight junctions leading to hyperpermeability [19,20]. By using rodents as a laboratory TPN model, a variety of aberrantly activated signaling pathways have been identified, including PI3K/pAkt [21], TLR4/EGF [22] and NF-κB/MLCK [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, FAO seems to be deactivated in those SBS patients with intestinal failure compared to their counterparts with intestinal adaption. Given a growing body of evidence linking PN‐induced villus atrophy to intestinal failure, 34–36 we then asked by what kind of mechanism intestinal FAO was functionally inhibited in these SBS patients and PN piglets.…”
Section: Discussionmentioning
confidence: 99%